Effect of vitamin E succinate as a differentiation agent on the efficacy of 5-ALA-PDT on prostate cancer cells in culture - Mohseni Kouchesfehani, Homa; Nabiuni, Mohammad; Majlesara, Mohammad Hossein; Amini, Elahe; Irian, Saeed (Archives of Advances in Biosciences, 2011)
Photodynamic Therapy (PDT) using 5-aminolevulinic acid (5-ALA)-induced protoporphyrin IX (PpIX) has been considered as a new method for treating neoplasms. However, ALA-PDT is suboptimal for thick tumors. Searching for new approaches, we investigated the effect of adding differentiation therapy (DT) with Vitamin E succinate (VES) to PDT in human prostate LN-CaP-FGC10 cancer cells in vitro. The purpose of DT was to reverse the lack of differentiation in cancer cells and to enhance the effectiveness of ALA- dependent PDT. Three groups of cells were grown on RPMI1640 culture medium supplemented with 10% FBS. The cells included: ALA-PDT cells, which received 0.3 mM ALA for 4 hours at dark, and exposed to 532 nm, 50 mW Nd-YAG laser beam for 3 min; DT+ALA-PDT cells, which received 6 µg/ml VES for 24, 48 and 72 hours, followed by the addition of 0.3 mM ALA for 4 h and exposure to Nd-YAG laser beam for 3 min; control cells which were untreated. After 24 h, the percentage of cell viability was determined by MTT assay. Accumulation of PpIX was measured by spectrophotometry and fluorescent microscopy. Mechanism of induced cell death was investigated via Hoechst staining. The combination of both factors (VES and 5-ALA) lead to a significant increase in cell death after 72 h. Induction of differentiation augmented PpIX accumulation in cells treated with ALA. Elevated intracellular PpIX levels resulted in an enhanced lethal photodynamic sensitization of VES plus ALA-treated cells after 72 h. Apoptotic cell death by both ALA-PDT and VES-ALA-PDT was confirmed by Hoechst staining. Our data suggest that VES used in combination with 5-ALA may provide a new combinatorial approach for treating certain cancers.